Antimicrobial activity of encapsulated spent coffee ground extract-incorporated chitosan films - Mahapol, Sirapat; Sripreechasak, Paranee; Punbusayakul, Niramol (Asia-Pacific Journal of Science and Technology, 2024)
This work aimed to compare antimicrobial activity of chitosan films containing encapsulated (eSCGE-CH film) and non-encapsulated spent coffee ground aqueous extracts (SCGE-CH film). Chitosan films with eSCGE and SCGE at SCGE equivalent concentrations of 0, 0.5, 0.75 and 1.0% (w/v) were prepared. The antimicrobial activity of eSCGE-CH and SCGE-CH films were evaluated by a drop-test method against some potent food pathogens, including Gram-positive bacteria. (Staphylococcus aureus TISTR2329 and Bacillus subtilis TISTR1984) and Gram-negative bacteria (Escherichia coli TISTR527 and Salmonella typhimurium TISTR2519). The eSCGE-CH film showed a higher inhibitory effect against S. aureus B. subtilis and S. typhimurium than the SCGE-CH film, with S. typhimurium being the most susceptible bacteria compared to the others (p ≤ 0.05). These results indicate that encapsulation could enhance the antimicrobial activity of the SCGE in the CH film suggesting the potential feasibility of the eSCGE-CH film as an antimicrobial packaging for food applications.